Are sustainability-linked loans designed to effectively incentivize corporate sustainability? A framework for review - Alix Auzepy; Christina E. Bannier; Fabio Martin (Goethe University Frankfurt, Center for Financial Studies (CFS), 2023)
The issuance of sustainability-linked loans (SLLs) has grown exponentially in recent years. Using a scoring methodology, we examine the underlying key performance indicators of a large sample of SLLs and analyze whether their design creates effective incentives for improving corporate sustainability performance. We demonstrate that the majority of loans fails to meet key requirements that would make them credible instruments for generating effective sustainability incentives. These findings call into question the actual sustainability impact that may be achieved through the issuance of ESG-linked debt.
urn:nbn:de:hebis:30:3-681448
Keywords: G21; G32; M14; 330; Sustainability-Linked Loans; sustainability KPIs; ESG lending; ESG loans; sustainable finance